A comparative analysis for optimal placement and sizing of distributed generator in grid connected and islanded mode of microgrid. (16th February 2021) - Kumar, Ankur; Choudhary, Niraj Kumar; Singh, Nitin
Distributed generation offers a promising solution to the ever-increasing power demand. Other than supplying power it also reduces the power losses and improves the voltage regulation of the line. The performance of the distribution network with DG gets affected by its location, number of generators, and size. This paper describes separate techniques for estimation of optimal location and size of the DG's using power loss index (PLI) method and radial correction factor (RCF) in IEEE-15 bus radial distribution system. The performance of each method is tested for both the operating modes, i.e., grid connected and islanded mode of microgrid. Further, the optimal placement of capacitors is also done using voltage stability index (VSI) method for both the configurations. The performance of the proposed techniques is analysed by comparing the voltage profile and real power loss before and after the DG placement in the network. A comparative study of optimal location and size of DG is also presented considering the features; minimum bus voltage, real and reactive power losses using genetic algorithm (GA) and artificial bee colony (ABC) algorithms.